Treatment landscape from first- to third-line therapy and quality of life data of patients with pancreatic cancer from the prospective German PARAGON (Platform for Outcome, Quality of Life, and Translational Research on Pancreatic Cancer) registry (IKF-PARAGON study) - Götze, Thorsten; Al-Batran, Salah-Eddin; Liersch, Ruediger; Scheuer, Lars; Goehler, Thomas; Kaiser, Ulrich; Denzlinger, Claudio; Brandl, Stephan; Pink, Daniel; Uhlig, Jens; Maasberg, Michael; Loose, Maria; et al. (International journal of cancer, 2025)
Pancreatic cancer (PCA) is the third leading cause of cancer-related death in Europe. Despite recent therapeutic advances, patients experience rapid health deterioration. Based on previous results, the Platform for Outcome, Quality of Life, and Translational Research on Pancreatic Cancer - PARAGON (NCT04119362) was initiated to investigate the whole life cycle of PCA patients. Between November 2019 and October 2021, 469/479 screened patients were enrolled in 46 sites. Demographic, clinical, and quality of life (QoL) data were collected. The treatment landscape was depicted using Sankey diagrams. Median overall survival (mOS) for all patients in first line was 10.6 months (95% confidence interval [CI], 9.2-11.7 months). With mFOLFIRINOX as first-line treatment, mOS was 11.3 months (95% CI, 8.6-13.5 months), with gemcitabine/nab-paclitaxel 10.5 months (95% CI, 8.3-12.9 months). The mean Global Health Status for patients that proceeded from first to second line did not substantially deteriorate during first line. Predictive variables for proceeding from first to second-line therapy were reasons for ending first-line treatment (patient's wish, toxicity, and progressive disease) and age. In summary, we were able to show in detail patient flows and QoL data throughout all therapy lines, which will help to further understand the major clinical checkpoints of the disease.